IMPACT OF CLIMATE CHANGE ON GULLY EROSION FORMATION IN GOMBE TOWN, NORTH EAST NIGERIA - Mbaya, Lazarus A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2016)
The processes involved in the impact of climate change on soil erosion by water were examined. Climatic data were collected from Gombe State University Meteorological station and National Meteorological station Gombe. Climatic elements collected were daily, monthly and annual rainfall, minimum and maximum temperature; evaporation, soil and grass temperature. Data spanning over 4 decades, from 1970 – 2013 were obtained from the two stations. Data collected were analyzed and presented in time series. Results revealed that climatic change have accelerated soil erosion directly through increases in surface air temperature and decreases in rainfall regimes, and indirectly through changes in vegetation and surface cover. Furthermore there was an increase in soil and grass temperature that have impacted on soil erosion through changes in vegetation and soil organic matter. It was suggested that as climate change will continue in the 21st century and beyond, planting of drought resistance plant such as Pitadeniastrum africanum (kashe kwari or kafi kansila), can effectively help in gully erosion control.